THE PROBLEM OF CHILDHOOD OBESITY AND THE RESPONSIBILITY OF PRIMARY CARE PROVIDERS: A REVIEW - Wright, Melissa A; Jones, Jessica L (LIFE: International Journal of Health and Life-Sciences, 2017)
Obesity rates are at epidemic levels throughout the world, and this concerning trend has not been exclusive to adults. Throughout the world, the prevalence of childhood obesity has risen to epidemic proportions over the last fifty years. These children are at high risk for multiple comorbidities affecting all organ systems. In addition to the concerning impacts on health, the obesity-related costs and burdens of healthcare on society are staggering. While the problem is becoming increasingly recognized, much is needed to be done to protect America’s youth from growing obesity rates. As proponents of children’s health, it is thus the responsibility of primary care providers to understand, prevent, recognize, and manage childhood obesity.